2009
DOI: 10.2478/s11696-008-0093-0
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effect of fluid elasticity on a cake filtration process

Abstract: The paper is concerned with the constant pressure cake filtration of suspensions in viscoelastic fluids. The filtration equations, based on the capillary hybrid model for power law fluid flow, were used for the description of this type of filtration. Filtration experiments with suspensions of nearly spherical polystyrene particles Krasten in viscoelastic aqueous solutions of polyacrylamide Praestol were carried out at constant pressure in a laboratory cylindrical filtration unit. The fluid rheological properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…It is expected that the elastic effect decreases progressively and the flow behavior of fluid changes to purely viscous by virtue of decrease of filtration rate [2]. However, the results of our experimental investigation of the constant pressure cake filtration of Krasten polystyrene particles from viscoelastic aqueous solutions of polyacryl amide Praestol show that in the final period of filtration, the contribution of elastic effect to the pressure drop in the filter cake cannot be negligible [3].…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…It is expected that the elastic effect decreases progressively and the flow behavior of fluid changes to purely viscous by virtue of decrease of filtration rate [2]. However, the results of our experimental investigation of the constant pressure cake filtration of Krasten polystyrene particles from viscoelastic aqueous solutions of polyacryl amide Praestol show that in the final period of filtration, the contribution of elastic effect to the pressure drop in the filter cake cannot be negligible [3].…”
Section: Introductionmentioning
confidence: 73%
“…In the work [3], we have shown that the total pressure drop 'p ve for the flow of viscoelastic filtrate through filter cake and filter screen can be given by the sum , , …”
Section: Filtration Equationmentioning
confidence: 99%
“…However, in their 2001 review, Chhabra et al [41] pointed out the persistent lack of definitive and quantitative information available on the role of viscoelasticity and of the effects arising from polymer/wall interactions, polymer retention, etc. Accordingly, from the results of frontal filtration experiments involving non-diluted solutions of polyacrylamides, Surý and Machač [42] stress on the significant contribution of polymers viscoelasticity (due to extensional deformations) to the control of the filtration process. Regarding more specifically WSP flow in porous media in the Darcy regime and under constant flow rate conditions, comprehensive reviews have been carried out by Sorbie [43] and Chauveteau and Sorbie [44].…”
Section: Nomenclaturementioning
confidence: 99%